Pemanfaatan Lahan Sempit dengan Penanaman Hidroponik untuk Peningkatan Jumlah Ruang Terbuka Hijau di Jagakarsa - Davilla Prawidya Azaria; Ali Imran Nasution; Anni Alvionita Simanjuntak; Gilang Abi Zaifa (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
One of the major problems of urban people has been a need for more knowledge about utilizing narrow spaces around houses to increase green open spaces (Ruang Terbuka Hijau or RTH). People must be able to utilize limited land to the best of their abilities in order to benefit the community themselves. This community service activity aims to educate the community about optimizing limited and narrow land to increase the number of green open spaces using hydroponic methods in the Ciganjur area, Jagakarsa. The implementation method of this activity consists of three stages: preparation, execution, and implementation. The results showed, which involved 20 participants from the group of women involved in PKK and the community in general in Ciganjur, Jagakarsa, provide education and skills to the community regarding the utilization of narrow land with hydroponic methods to increase the number of green open spaces and improving the environment quality as well. Participants in the activity also acquire skills in applying hydroponic planting methods for using limited spaces.